Structural and functional properties of microbial communities in the annual sea-ice at Terra Nova Bay (Ross Sea – Antarctica). - GUGLIELMO L.; CARRADA G. C.; CATALANO G.; DELLANNO A.; FABIANO M.; LAZZARA L.; PUSCEDDU A.; SAGGIOMO V.; MANGONI, OLGA (2000)
Studies on the chemical and biological properties of annual pack ice at a coastal station in Terra Nova Bay (74°41.72'S, 164°11.63'E) were carried out during austral spring at 3-day intervals from 5 November to 1 December 1997. Temporal changes of nutrient concentrations, algal biomasses, taxonomic composition, photosynthetic pigment spectra and P±E relationships were studied. Quantity, composition and degradation rates of organic matter in the intact sea ice were also investigated. In addition, microcosm experiments were carried out to evaluate photosynthetic and photo-acclimation processes of the sympagic flora in relation to different light regimes. High concentrations of ammonia were measured in four ice-cores (weighted mean values of the cores ranged from 4.3 ± 1.9 uM to 7.2 ± 3.4 uM), whereas nitrate and phosphate displayed high concentrations (up to 35.9 uM and 7.6 uM, respectively) only in the bottom layer (135±145 cm depth). Particulate carbohydrate and protein concentrations in the intact sea ice ranged from 0.5 to 2.3 mg l-1 and 0.2 to 2.0 mg l-1, respectively, displaying a notable accumulation of organic matter in the bottom colored layer, where bacterial enzymatic activities also reached the highest values. Aminopeptidase activity was extremely high (up to 19.7 uM l-1 h-1 ± 0.05 in the bottom layer),suggesting a rapid turnover rate of nitrogen-enriched organic compounds (e.g. proteins). By contrast, bacterial secondary production was low, suggesting that only a very small fraction of mobilized organic matter was converted into bacterial biomass (<0.01%o). The sympagic autotrophic biomass (in terms of chlorophaeopigments) of the bottom layer was high, increasing during the sampling period from 680 to 2480 lg l-1. Analyses of pigments performed by HPLC, as well as microscope observations, indicated that diatoms dominated bottom communities. The most important species were Amphiprora sp. and Nitschia cfr. stellata. Bottom sympagic communities showed an average PB max of 0.12 mgC mg Chl-1 and low ...